Defining Regional Climate Leadership: Learning from Comparative Analysis in the Asia Pacific. Issue 4 (8th August 2018) - Crowley, Kate; Nakamura, Akihiro
Abstract: Comparative analysis of national mitigation and adaptation efforts generates transferable climate policy learning, which helps meet global climate policy aspirations to avoid dangerous climate change. This article proposes a novel framework for assessing the contributions of regional climate leadership to such efforts in the Asia Pacific, and operationalizes that framework through comparative analysis of Japanese and Australian initiatives. It argues that the climate policy efforts of developed nations such as these should include efforts to assist less developed regional neighbors because of the extreme vulnerability of the Asia Pacific to climate change.